Firms' knowledge‐sharing strategies in the global innovation system: empirical evidence from the flat panel display industry - Spencer, Jennifer W. (Strategic Management Journal, 2003)
Abstract This paper explores the relationship between firms' strategies to share knowledge with their innovation system and innovative performance. The empirical analysis showed that many firms designed strategies to share technological knowledge with competitors, and those firms that shared knowledge with their innovation system earned higher innovative performance than firms that did not share knowledge. In addition, firms that interacted with their global innovation system earned higher innovative performance than firms that interacted with only their national innovation system. These results should help managers and researchers understand how to devise technology strategies in globally integrated industries. Copyright © 2003 John Wiley & Sons, Ltd.